Needle Insertion with Duty-Cycled Rotation into Multiple Media - Lehocky, Craig A. (2012)
Thin, flexible needles can be steered along nonlinear paths to reach deep anatomical structures within the human body. This study builds upon previous work involving steering of bevel-tipped needles by inserting while rotating in a duty-cycled fashion. Here we investigate how needle material and radius, duty cycle, and tissue stiffness affect needle curvature. Needles were inserted into media while rotated at a specified duty cycle and the curvature was measured. A linear relationship between duty cycle and curvature was observed across all needle materials and radii, and tissue stiffnesses. Following these observations, we developed a model that encapsulates needle and tissue parameters in order to predict the duty cycle needed to achieve a desired curvature.